2014
DOI: 10.1371/journal.pone.0100241
|View full text |Cite
|
Sign up to set email alerts
|

Is the Conditioned Pain Modulation Paradigm Reliable? A Test-Retest Assessment Using the Nociceptive Withdrawal Reflex

Abstract: The aim of this study was to determine the reliability of the conditioned pain modulation (CPM) paradigm assessed by an objective electrophysiological method, the nociceptive withdrawal reflex (NWR), and psychophysical measures, using hypothetical sample sizes for future studies as analytical goals. Thirty-four healthy volunteers participated in two identical experimental sessions, separated by 1 to 3 weeks. In each session, the cold pressor test (CPT) was used to induce CPM, and the NWR thresholds, electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 58 publications
(112 reference statements)
4
65
1
Order By: Relevance
“…This reliability was shown by Biurrun Manresa et al 5 for nociceptive withdrawal reflexes as test stimulus; Jurth et al 35 found good reliability for both psychophysical and electrophysiological measures of the same reflex. Less good reliability was reported by Olesen et al 68 for psychophysical measurements.…”
Section: Methodsmentioning
confidence: 62%
“…This reliability was shown by Biurrun Manresa et al 5 for nociceptive withdrawal reflexes as test stimulus; Jurth et al 35 found good reliability for both psychophysical and electrophysiological measures of the same reflex. Less good reliability was reported by Olesen et al 68 for psychophysical measurements.…”
Section: Methodsmentioning
confidence: 62%
“…An increase in pressure pain detection threshold immediately after cold pressure test was an indication of functioning CPM. 12 …”
Section: Conditioned Pain Modulationmentioning
confidence: 99%
“…Conditioned pain modulation was measured as the difference in pressure pain detection threshold between measurements after and before the cold pressor test (ΔCPM). 12,13 Cutaneous Single Electrical Stimulation Electrical stimulation of the sural nerve was performed through electrodes placed distal to the lateral malleolus. A 25millisecond, train-of-5, 1 millisecond, square-wave impulse (perceived as 1 stimulus), was delivered by a computer-controlled constant current stimulator (Digitimer DS7A; Neurospec, Letchworth Garden City, UK).…”
Section: Pressure Stimulation After Cold Pressor Testmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the electrical stimulation applied directly over the sural nerve is often associated with substantial pain and discomfort. In both healthy volunteers and pain patients, a number of subjects find the painful stimulation intolerable and the assessment cannot be completed (Banic et al, 2004;Biurrun Manresa et al, 2014b;Sterling et al, 2008). In this way, the practical applicability of the NWR-T as a clinical measure of nociceptive excitability is reduced.…”
Section: Introductionmentioning
confidence: 99%